Drivers of civil society organisations' participation in Ghana's governance processes. Issue 8 (17th November 2019) - Antwi-Boasiako, Joseph
ABSTRACT: Governance has been described as an institutionalised mode of social coordination to provide collective goods. In Ghana, governance involves various stakeholders such as the government, state agencies, development partners, the private sector, and civil society organisations (CSOs). While government's participation in governance is mandatory, stakeholders like CSOs may be driven by certain factors to participate in the governance process. Using stakeholder analysis as its analytical lens, this article reports on a study that adopted a qualitative research approach and found that CSOs in Ghana are driven by their contribution to the development of a just society, the mandate of the organisation, funding, and recognition.